Vitamin A Protects the Preterm Lamb Diaphragm Against Adverse Effects of Mechanical Ventilation - Song, Yong; Dahl, MarJanna; Leavitt, Wendy; Alvord, Jeremy; Bradford, Calan Y.; Albertine, Kurt H.; Pillow, J. Jane (Frontiers in Physiology, 2018)
Background: Preterm infants are deficient in vitamin A, which is essential for growth and development of the diaphragm. Preterm infants often require mechanical ventilation (MV) for respiratory distress. In adults, MV is associated with the development of ventilation-induced diaphragm dysfunction and difficulty weaning from the ventilator. We assessed the impact of MV on the preterm diaphragm and the protective effect of vitamin A during MV. Methods: Preterm lambs delivered operatively at ∼131 days gestation (full gestation: 150 days) received respiratory support by synchronized intermittent mandatory ventilation for 3 days. Lambs in the treated group received daily (24 h) enteral doses of 2500 IU/kg/day vitamin A combined with 250 IU/kg/day retinoic acid (VARA) during MV, while MV control lambs received saline. Unventilated fetal reference lambs were euthanized at birth, without being allowed to breathe. The fetal diaphragm was collected to quantify mRNA levels of myosin heavy chain (MHC) isoforms, atrophy genes, antioxidant genes, and pro-inflammatory genes; to determine ubiquitin proteasome pathway activity; to measure the abundance of protein carbonyl, and to investigate metabolic signaling. Results: Postnatal MV significantly decreased expression level of the neonatal MHC gene but increased expression level of MHC IIx mRNA level (p < 0.05). Proteasome activity increased after 3 days MV, accompanied by increased MuRF1 mRNA level and accumulated protein carbonyl abundance. VARA supplementation decreased proteasome activity and FOXO1 signaling, down-regulated MuRF1 expression, and reduced reactive oxidant production. Conclusion: These findings suggest that 3 days of MV results in abnormal myofibrillar composition, activation of the proteolytic pathway, and oxidative injury of diaphragms in mechanically ventilated preterm lambs. Daily enteral VARA protects the preterm diaphragm from these adverse effects.